Patients with hip resurfacing arthroplasty are not physically more active than those with a stemmed total hip - Jelsma, Jetse; Schotanus, Martijn G M; Buil, Ivo T A F; Kuijk, Sander M J Van; Heyligers, Ide C; Grimm, Bernd (Acta Orthopaedica, 2020)
Background and purpose — Hip resurfacing arthroplasty (HRA) was designed for the highly active patient because of the various theoretical advantages compared with stemmed total hip arthroplasty (THA), but has shown high failure rates. Physical activity (PA) after arthroplasty is frequently determined with the use of questionnaires, which are known for their subjective nature, recall bias, and ceiling effect. These disadvantages are not applicable to physical activity monitoring (AM) using sensors. We compared objectively measured PA at long-term follow-up in a matched cohort of HRA and stemmed THA subjects. Patients and methods — We compared 2 groups of 16 patients (12 males) in each group, one having received unilateral HRA (median age 56 years at surgery) and a matched group having received unilateral stemmed THA with a small diameter femoral head (28 mm) on conventional polyethylene (median age 60 years at surgery) with osteoarthritis as indication for surgery, 10 years after surgery. Groups were matched by sex, age at surgery, and BMI. The daily habitual PA was measured over 4 consecutive days in daily living using a 3-axis accelerometer, gyroscope, and magnetometer. Both quantitative parameters (time standing, sitting, walking, number of steps, and sit–stand transfers) and qualitative parameters (walking cadence) were determined. Results — The AM was worn for a median 13 (11–16) hours per day. The median daily step count was 5,546 (2,274–9,966) for the HRA group and 4,583 (1,567–11,749) for the stemmed THA-group with 39 (21–74) versus 37 (24–62) daily sit–stand transfers respectively. The other PA parameters were also similar in both groups. Interpretation — We found similar median PA levels and also identical ranges. While short-term effects may exist, ageing and related behavioral adaptations or other effects seem to render the theoretical activity benefits from HRA irrelevant at longer follow-up.